On the material behaviour in a progressive microforming process - Phee, Jeremy Jun Kai. (2013)
In the 21st century, miniaturization has emerged in several fields of technology, leading to the development of mini products and devices for industries such as electronics, communication and optics. With increasing demand, many researches have been initiated worldwide in microforming processes.